Evaluación de la producción forrajera del ryegrass perenne diploide y tetraploide sembrado con un retenedor de agua a 0, 5, 10 y 15 cm de profundidad y su impacto en la producción ganadera en el cantón Latacunga, parroquia Alaquez - Mangui García, Erick Ricardo (2021)
The present research work was carried out in the Alaquez parish of Latacunga, with an altitude of 3477 meters above sea level at an average temperature of 12 ° C, for the present research project 6 cm thick, 80 cm long glass containers were used, 40 cm high and 20 cm wide, hydrogel granulated water retainers were placed at different depths ranging between 0, 5, 10, 15 cm deep, three repetitions were carried out, after which the two types of Diploid and tetraploid perennial ryegrass with the objective of observing at what depth the hydrogel water container has a better effectiveness once the sowing has been carried out, the germination time of the seed was evaluated, at what depth a better rooting takes place, the time of development and production of pastures dry matter (DM) giving us as a result that the germination time, no greater impact since the seeds have germinated at the same t ime since they were sown at the same depth in the three repetitions and in the different treatments, in terms of rooting, we observed that the greater the depth of sowing of the hydrogel, the better use of moisture and development of the root giving us as a result that treatment number 4, that is, with the hydrogel at 15 cm depth, is the most optimal for the development of the root, as regards the development of the plant and obtaining the third leaf, we observe that the treatment Number three with the hydrogel at a depth of 10 cm has a faster maturation development of the plant and finally, in terms of obtaining dry matter (DM) we obtained as a result that treatment number 1 and 4, that is, the Hydrogel seeded at a depth of 0 and 15 cm in depth has a better obtaining of dry matter weight, as a result that in the three repetitions the treatment number 4 with e The hydrogel at a depth of 15 cm is the most optimal for the production of grasses.